Oral contraceptive use and abortion before first term pregnancy in relation to breast cancer risk. - Vessey, M. P. (Nature Publishing Group, 1982)
A recent publication from California in this journal has suggested that both prolonged oral contraceptive use and abortion before first term pregnancy increases the risk of breast cancer in young women. Data are presented on 1176 women aged 16-50 years with breast cancer, interviewed in London or in Oxford, together with a like number of matches control subjects. The results are entirely reassuring, being, in fact, more compatible with protective effects than the reverse. Possible reasons for the differences between the 2 sets of data are discussed.